Effect of inhaled frusemide on responses of airways to bradykinin and adenosine 5'-monophosphate in asthma. Issue 5 (May 1994) - Rajakulasingam, K; Polosa, R; Church, M K; Howarth, P H; Holgate, S T
Abstract : BACKGROUND--Inhaled frusemide exerts a protective effect against bronchoconstriction induced by several indirect stimuli in asthma. This effect could be caused by interference with neural pathways. The effect of inhaled frusemide on bronchoconstriction induced by inhaled bradykinin, which is thought to cause bronchoconstriction via neural mechanisms, was studied and compared with the effects of adenosine 5'-monophosphate (AMP) which probably produces its airway effects by augmenting mast cell mediator release and interfering with neural pathways. METHODS--Patients first underwent AMP and bradykinin challenges. They were then studied in a randomised, placebo controlled, double blind fashion. Ten atopic asthmatic subjects, studied on four days, were pretreated with inhaled frusemide (40 mg) or placebo for 10 minutes, five minutes before challenge with increasing concentrations of nebulised AMP or bradykinin. RESULTS--On the open visit days the provocative concentrations required to reduce forced expiratory volume in one second (FEV1) by 20% from baseline (PC20) for AMP and bradykinin were 16.23 (1.42-67.16) and 2.75 (0.81-6.6) mg/ml. There was a significant correlation between baseline AMP and bradykinin PC20 values. For AMP the geometric mean PC20 values following pretreatment with inhaled frusemide and matched placebo were 80.97 (9.97- > 400.0) and 14.86 (2.6-104.6) mg/ml respectively (95% CI 0.49 to 0.98). For bradykinin the geometric mean PC20 values following pretreatment with inhaled frusemide and matched placebo were 13.22 (2.53- > 16.0) and 2.52 (0.45-5.61) mg/ml respectively (95% CI 0.43 to 1.01). Frusemide afforded 5.45 and 5.24 fold protection against AMP and bradykinin-induced bronchoconstriction respectively. Furthermore, there was a significant correlation between protection afforded to the airways against AMP and bradykinin. CONCLUSIONS--These data suggest that inhaled frusemide affords protection against bradykinin-induced bronchoconstriction which is comparable to that against AMP, supporting a common mechanism of action for frusemide.